Kebijakan Penanganan Kekerasan terhadap Perempuan pada Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Malang: Indonesia - Utaminingsih, Alifiulahtin; Fitri, Nur Zanuba Arifa’ul (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
High reports of cases of violence experienced by women really need attention from the government. Policies are needed that can provide protection, treatment, prevention and provide facilities to help victims of violence. As an effort to overcome the problem of violence against women, Malang regency has established a policy of protection of women from violence as stated in Regional Regulation No. 3 of 2009 on the Protection of Women and Children Victims of violence. This study aims to determine and analyze how the implementation of the policy of handling violence against women in Malang regency. The theory used in this study is the theory of policy implementation perspective G. C. Edward III had four variables: communication, resources, disposition, and bureaucratic structure. The research method used in this study is descriptive qualitative. The results of the study showed the implementation of policy implementation, as follows: 1) the implementation of communication carried out by DP3A internally and with external institutions is good enough, but there are obstacles that have not occurred evaluation of socialization that has been done to the target group; 2) in terms of resources there is still a shortage of; 3) the tendency or disposition of implementers and officials is good enough, but still have to increase the sensitivity of gender; 4) the hierarchy of bureaucratic structures in DP3A is not too far away, but still need better coordination between officials to implementers so that policy implementation runs optimally. Keywords: Policy, Handling, Violence, Women